Rainwater harvesting system: the economical placement of rainwater collective tank for terrace house / Maznie Maheera Misron - Misron, Maznie Maheera (Faculty of Architecture, Planning and Surveying, 2015)
The application of an appropriate rainwater harvesting technology can make possible to the utilization of rainwater as a valuable and necessary water resource. This research aim to discover the suitability and economical placement for rainwater collective tank for rainwater harvesting system in terrace house. Most of the existing terrace house having limited space and suffered high and insufficient amount of cost for implementing the system. Thus, new projects especially the projects of green building homes nowadays have increase to encourage of never wasted the nature’s precious resources such as rainwater. The rainwater harvesting system were installed at the terrace house thus can be used to collect rainwater for use in gardening and toilet flushing. The performance is judged from the instrument which-is developed through theresearch framework. The discussion starts with establishing the research concept by determine the overview of Rainwater Harvesting System in Malaysia. The research started with the literature reviews on rainwater harvesting system and rainwater collective tank. The assessment framework of this study has been developed as guide for this research to drive the research flow and the objective achievement. Two other instruments used in this research to accessed the performance and maintenance of each placement of rainwater collective tank for residential building. The instrument are questionnaire survey and interview had become the main data collection of the study. This is important to ensure the successful of this research.